PERK regulates Gq protein-coupled intracellular Ca2+ dynamics in primary cortical neurons. Issue 1 (December 2016) - Zhu, Siying; McGrath, Barbara; Bai, Yuting; Tang, Xin; Cavener, Douglas
Abstract PERK (EIF2AK3) is an ER-resident eIF2α kinase required for behavioral flexibility and metabotropic glutamate receptor-dependent long-term depression via its translational control. Motivated by the recent discoveries that PERK regulates Ca2+ dynamics in insulin-secreting β-cells underlying glucose-stimulated insulin secretion, and modulates Ca2+ signals-dependent working memory, we explored the role of PERK in regulating Gq protein-coupled Ca2+ dynamics in pyramidal neurons. We found that acute PERK inhibition by the use of a highly specific PERK inhibitor reduced the intracellular Ca2+ rise stimulated by the activation of acetylcholine, metabotropic glutamate and bradykinin-2 receptors in primary cortical neurons. More specifically, acute PERK inhibition increased IP3 receptor mediated ER Ca2+ release, but decreased receptor-operated extracellular Ca2+ influx. Impaired Gq protein-coupled intracellular Ca2+ rise was also observed in geneticPerk knockout neurons. Taken together, our findings reveal a novel role of PERK in neurons, which is eIF2α-independent, and suggest that the impaired working memory in forebrain-specificPerk knockout mice may stem from altered Gq protein-coupled intracellular Ca2+ dynamics in cortical pyramidal neurons.